Uniqueness Theorem for Hilbert Transform for Boehmians - Abhishek Singh (Scientia Series A: Mathematical Sciences, 2025)
In this paper a uniqueness theorem is proved for the Hilbert transform for the Boehmians of analytic function by using a relation between the Hilbert transform and the Fourier transform. Hilbert transform of Boehmians of analytic type is also discussed.